(untitled) (Isagoge - Journal of Humanities and Social Sciences, 2022)
“The process is not an end in itself” (DIDIER). The process is an instrument for the satisfaction of rights and must be accessible to anyone, thus promoting justice and social peace expected by all who take their demands to the Judiciary. The analysis made about access to justice led to the conclusion that often excessive formalism, disinformation and disbelief keep those legitimated from submitting demands to the State for consideration, with the need to strengthen the institution for a lesser discredit and also to use of the social scope by the Judge in the application of the law to concrete cases.